The policy of European and Euro-Atlantic integration as a key factor for Ukraine’s transformation - Pipchenko, Nataliya; Makarenko, Ievgeniia; Ryzhkov, Mykola; Zaitseva, Mariia (European Spatial Research and Policy, 2021)
The article explores the practice perspectives of European and Euro-Atlantic integration for the West’s Eastern neighbours with a focus on Ukraine in the main directions of cooperation: political, economic, security, and communication. It has been established that Eastern Partners show a dissimilar political interest in rapprochement with the EU and NATO due to the existence of different foreign policy goals. The EU’s Association Agreements with Ukraine, Georgia, and Moldova are primarily aimed at defending the European integration, so the states are interested in developing close trade relations, and in achieving open and sustainable economic growth. The results have shown that Ukraine’s deepening Euro-Atlantic ties are a continuation of the European course of the state’s development, since the interaction with the EU and NATO aims to expand transatlantic relations and create updated security formats. The article also analyses the mechanisms of improving the efficiency of the communication between the EU, NATO and Ukraine by informing the public about the progress of Ukraine’s integration into relevant structures, the reforms of the economic and security sectors of Ukraine, and its participation in the Alliance’s non-military initiatives. The findings suggest that the improvement of public communication tools increases the involvement of governments in implementing integration policy goals and identifying issues that need a further response. Additionally, the Ukrainian government should strategically focus on ensuring and implementing practical measures aimed at shaping the image of Ukraine as an intent partner that adheres to its political commitments.